Reflectarray Antenna with Radar Cross-Section Reduction - Misran, Norbahiah; Ismail, M. Y.; Islam, M. T. (International Journal of Integrated Engineering, 2010)
This paper presents the design of a low RCS reflectarray at 8.52 GHz by replacing the solid metal sheet behind the antenna with a band stop frequency selective surface. A 50 element linear array of omni-directional elements was used to simulate the far field pattern of a reflectarray with f/D=0.325 in the plane of the elements to assess the effect of an imperfect aperture distribution on the gain and sidelobe levels. It is found that the reflection loss variation across the aperture does not have a significant effect on the radiation pattern of the antenna, because for the layout that was studied, only a few of resonant loops were predicted to give a significantly different loss than the others in the array. Simulated and measured results show that the ‘in-band’ reflection phase response of the structure with metal ground plane and with a periodic FSS ground plane is very similar, however the periodic ground plane reduces the ‘out of band’ reflectivity by more than 4 dB, thereby decreasing its RCS profile to these signals.